2018
DOI: 10.1103/physrevc.97.054605
|View full text |Cite
|
Sign up to set email alerts
|

Large longitudinal spin alignment generated in inelastic nuclear reactions

Abstract: Large longitudinal spin alignment of E/A=24 MeV 7 Li projectiles inelastically excited by Be, C, and Al targets was observed when the latter remain in their ground state. This alignment is a consequence of an angular-momentum-excitation-energy mismatch which is well described by a DWBA cluster-model (α + t). The longitudinal alignment of several other systems is also well described by DWBA calculations, including one where a cluster model is inappropriate, demonstrating that the alignment mechanism is a more g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…The widths of the observed E * T arget peaks are consistent with the simulated resolution for this quantity. Similar-shaped E * T arget distributions were observed for inelastic scattering of 7 Be (E/A=65.5 MeV) and 6 Li (E/A=36.6 MeV) projectiles on 9 Be targets [24] and for 7 Li projectiles on 9 Be, 12 C, and 27 Al targets at E/A=24 MeV [25,26]. The E * T arget =0 component has a more forward focused angular distribution than that of the tail component.…”
Section: Feeding From Proton-decayssupporting
confidence: 62%
“…The widths of the observed E * T arget peaks are consistent with the simulated resolution for this quantity. Similar-shaped E * T arget distributions were observed for inelastic scattering of 7 Be (E/A=65.5 MeV) and 6 Li (E/A=36.6 MeV) projectiles on 9 Be targets [24] and for 7 Li projectiles on 9 Be, 12 C, and 27 Al targets at E/A=24 MeV [25,26]. The E * T arget =0 component has a more forward focused angular distribution than that of the tail component.…”
Section: Feeding From Proton-decayssupporting
confidence: 62%
“…The spin of the target nucleus was shown to be unimportant in Ref. [3] where similar spin alignments for 7 Li excited state was observed with both a J=3/2 9 Be and a spin-zero 12 C target.…”
Section: Dwba Calculations and Spin Assignmentsmentioning
confidence: 65%
“…Previous studies of inelastic scattering with fast beams have shown the possibility of achieving strong spin alignment if the target nucleus remains in its ground state after the inelastic scattering [1][2][3][4]. Figure 3 shows the distributions of target excitation energy deduced from the center of mass of the p+ 12 N and 2p+ 11 C events assuming two-body kinematics for inelastic scattering reactions.…”
Section: B Decay Angular Distributionsmentioning
confidence: 99%
See 2 more Smart Citations